Does unemployment responsiveness to output change depend on age, gender, education, and the phase of the business cycle? - Mindaugas Butkus; Kristina Matuzeviciute; Dovile Rupliene; Janina Seputiene (Economies, 2020)
The impact of economic growth on unemployment is commonly agreed and extensively studied. However, how age and gender shape this relationship is not as well explored, while there is an absence of research on whether education plays a role. We apply Okun's law, aiming to estimate age-, gender- and educational attainment level-specific unemployment rate sensitivity to cyclical output fluctuations. Since the empirical literature provides evidence in favour of the non-linear impact of output change on the unemployment rate, supporting higher effects of recessions than that of expansions, we aim to enrich this analysis by estimating how the impact of positive/negative output change on the specific unemployment rate varies with the level of the total unemployment. The analysis is based on 28 European Union (EU) countries and covers the period of 1995-2019. The equations are estimated by least-squares dummy variables (LSDV), using Prais-Winsten standard errors. For the robustness check, we alternatively used Newey-West standard errors to address serial-correlations and heteroscedasticity, and the Arellano-Bond estimator for some specifications that assume dynamics in the panel. The results support previous findings of male- and youth-specific Okun's coefficients and reveal that they significantly stand out just over the periods of negative output change. Additionally, we find that educational attainment level is an important factor explaining the heterogeneity of unemployment reaction to output change.
Keywords: E24; E32; J16; 330; educational attainment level; European Union; gender; Okun's law; output change